Is temperature adversely related to economic development? Evidence on the short-run and the long-run links from sub-national data - Daniel Meierrieks; David Stadelmann (Energy Economics, 2024)
We examine the effect of rising temperatures on regional economic development, using annual sub-national data for over 1500 regions in 152 countries between 1990 and 2017. In a panel setting with region- and country-year fixed effects, we find no evidence of a homogeneous or heterogeneous effect of rising temperatures on economic development as measured by regional per capita income. Additionally, we find no non-linear relationship between temperature and economic development. We also employ a long-difference approach that is attuned to exploring the long-run relationship between rising temperatures and regional income. Results indicate that rising temperatures have a negative long-run impact on regional per capita income for a minority of regions located in countries with weak economic, legal and political institutions. Furthermore, these vulnerable regions experience a decline in long-term population and human capital development. The use of alternative regional per capita GDP data from 1950 onwards yields similar empirical results. Our findings suggest that negative economic effects of temperature increase with time, only becoming apparent in the long run for regions in already disadvantaged countries. Thus, country-specific conditions may moderate regional economic vulnerability to future temperature increases due to global climate change.
Keywords: O44; O47; Q54; R11; 330; Regional temperature; Regional per capita income; Sub-national data; Long-difference approach; Threshold models; Global warmin